EFFECT OF PITTING ON MESHING STIFFNESS OF GEARS - ZHAO Xin; ZHANG XiuHua; PU Jiang (Jixie qiangdu)
The change of meshing stiffness of gears is caused by the change of meshing position and meshing number between gears when the gears are running.The change of meshing stiffness reflects the change of meshing process of gears.When pitting occurs,the meshing stiffness of gears will change,which will lead to the change of vibration law of gearbox.This change can be used to judge whether the internal fault of gearbox is serious or not.According to the actual situation of pitting,pitting pits are set as elliptical sections.The meshing stiffness under pitting failure is calculated by potential energy method,and the influence of pitting location,size and depth on meshing stiffness is analyzed.The results show that pitting has no effect on the meshing stiffness of the non-pitting area under the gear teeth during the meshing process.The closer the pitting position is to the top of the gear teeth,the greater the impact on the meshing stiffness above the pitting gear teeth.The deeper the pitting pit is,the larger the area is,the more the meshing stiffness decreases,and the more obvious the influence of the area change on the meshing stiffness changes.